Cataract service redesign in the post-COVID-19 era. Issue 6 (23rd July 2020) - Lin, Pei-Fen; Naveed, Hasan; Eleftheriadou, Maria; Purbrick, Robert; Zarei Ghanavati, Mehran; Liu, Christopher
Abstract : COVID-19 pandemic of 2020 has impacted all aspects of clinical practice in the UK. Cataract services suffered severe disruption due to necessary measures taken to reduce elective surgery in order to release capacity to support intensive care requirements. Faced with a potential 50% increase in cataract surgery workload per week in the post-COVID-19 world, eye units should use this event to innovate, not just survive but to also evolve for a sustainable future. In this article, we discuss the inadequacies of existing service rationing options to tackle the COVID-19 cataract backlog. This includes limiting rationing based on visual acuity, limiting surgery to first or only seeing eyes, and postponing clinic and surgical dates according to referral dates. We propose units use the lockdown time to reset and develop a comprehensive patient-centred care pathway using principles of value-based healthcare: the cataract integrated practice units. Developing an agile surgical database that incorporates all aspects of patient need from education to follow-up in their individual cataract journey will allow units to react and plan quickly in the early phase of recovery and beyond. We also discuss the considerations units should bear in mind on telemedicine, modifications for face-to-face clinics, theatre organisation and options of expanding cataract throughput capacity. The pause in elective surgery due to the pandemic may have provided cataract services a rare opportunity to reset and transform cataract service pathways for the digital era.